Propuesta de gestión municipal de residuos sólidos del distrito de Tarapoto 2010 - Viena Sánchez, Segundo Uladislao (2011)
All the investigation carried out in the beautiful topic the management of Solid waste that is being made in several local governments of Peru and the world continues to be a rather complex issue and that until now has not been settled by any authority on duty, in any case very few municipalities that have led to successful experiences, in that regard. This research project known as "Proposal for Municipal Management of solid waste in the Tarapoto district 2010, it has to do basically all the System of Evaluation and management of solid wastes from municipal origin that is being generated in the city with the main objective of aspire to be one of the healthy municipalities of the San Martin department, in addition to contributing to the process of municipal environmental management that should be implemented on a compulsory basis as indicated by law under the National environmental Management System N°. 28245, at the same time the above mentioned law contemplates the diverse organs and institutional competitions that will have to be implemented across the local governments and also regional. In this sense, the Tarapoto Local government is a strong belief go step by step by implementing these processes that should have a positive impact on the quality municipal administrative as well as in the provision of their municipal services, such as for example, the phases of collection, transport and disposal of Solid Waste in the locality. On the other hand the Municipal authority has decided to approach a process of Municipal, Certification, in which it is necessary to elaborate technical documents, instruments of environmental management and elements databases for such an end; since the Ministry of the Environment today requires them; while it is true, this is a medium term process but it is good to begin with something in order to plan the sustainable development of the locality. With the systematization of the final report of the thesis we are contributing significantly to strengthen Environmental Management Local Municipal. Key words: environmental management, solid waste.